Detection of the staphylococcal enterotoxin D-like gene from staphylococcal food poisoning isolates over the last two decades in Tokyo - SUZUKI, Yasunori (J Vet Med Sci, 2015)
The plasmid is a very well-known mobile genetic element that participates in the acquisition of virulence genes, such as staphylococcal enterotoxins (SEs), via horizontal transfer. SEs are emetic toxins and causative agents in staphylococcal food poisoning (SFP). We herein identified the types of plasmids harbored by seven SFP isolates and examined their production of plasmid-related SE/SEl to determine whether the new types of plasmid-related SE or SE-like (SEl) toxins (i.e. SElJ and SER) were involved in SFP. These isolates harbored pIB485-like plasmids, and all, except for one isolate, produced SElJ and SER. The amount of SER produced by each isolate accounted for the highest or second highest percentage of the total amount of SE/SEl produced. These new types of plasmid-related SE/SEls as well as classical SE may play a role in SFP. The seven isolates were classified into two SED-production types; a high SED-production type (>500 ng/ml) and no SED-production type. A nucleotide sequencing analysis revealed that three plasmids harbored by the SED-non-producing isolates had a single-base deletion in the sed gene with a resulting stop codon (from 233 amino acids of the intact SED to 154 amino acids of the mutant SED (mSED)). A real-time reverse transcription-PCR analysis showed that the mRNA of the msed gene was transcribed in the isolates. If the msed gene was translated as a protein, mSED may act as an emetic toxin instead of intact SED.